FAKTOR KARAKTERISTIK IBU BERSALIN YANG MENGALAMI PERDARAHAN POSTPARTUM PRIMER DI RS PERMATA MADINA KABUPATEN MANDAILING NATAL PROVINSI SUMATERA UTARA - Ariska; Permata Sari, Diah; Br Napitupulu, Nova Isabella Mariance; Aruan, Lasria Yolivia (Midwifery And Complementary Care, 2025)
Background: Postpartum hemorrhage (PPH) is the leading contributor to maternal mortality worldwide, accounting for 50–75% of all emergency cases that occur during childbirth. Objective: Postpartum hemorrhage (PPH) is the leading contributor to maternal mortality worldwide, accounting for 50–75% of all emergency cases that occur during childbirth. Method: This study used a quantitative research method with a case-control study design. The sampling technique was purposive sampling, with a total of 68 samples. Data analysis was conducted using the chi-square test. Results: The results showed that the majority of primiparous mothers did not experience hemorrhage, with 60 individuals (88.2%). Most mothers with a birth interval of more than 5 years did not experience hemorrhage, totaling 60 individuals (88.2%). Additionally, most non-anemic mothers did not experience hemorrhage, with 40 individuals (58.8%). At a 95% confidence level, the p-values were 0.002, 0.001, and 0.001, respectively. Therefore, there is a significant relationship between these three variables and the incidence of primary postpartum hemorrhage. Conclusion: Midwives are encouraged to frequently provide education to women of childbearing age (WCA) to manage birth spacing and to undergo regular antenatal care check-ups. Keywords: Postpartum hemorrhage, birth interval, parity, anemia, pregnant women